STUDI KOMPARATIF USAHATANI TEMBAKAU MONOKULTUR DAN TUMPANG SARI DI KECAMATAN KLEDUNG KABUPATEN TEMANGGUNG - , Tantri Siwi Saptani, S. Sos ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Focus in this research are to know the influence factors on tobacco production in Kledung sub district Temanggung District, Compared tobacco farming income with monoculture and tumpangsari methods in Kledung sub district Temanggung district, Compared tobacco farming feasibility with monoculture and tumpangsari methods in Kledung sub district Temanggung district and Impact of tobacco farming concerning income distribution in Kledung sub district Temanggung district. The method used in this research is analysis descriptive methods. The respondent given by purposive sampling methods as many 60 respondent separate in 2 villages, that is 30 respondent from Kruwisan village and 30 respondent from Thalap village Kledung sub district Temanggung district. Aims of this research are (1) The influence factors on tobacco production are wide of land, seeds and planting system, (2) Income of tobacco farmer with monoculture method in Kruwisan village as many Rp 4.326.767 higher than tobacco farmer with tumpangsari method in Tlahap village as many Rp 1.143.660, (3) R/C value in Kruwisan village 2,08 and in Tlahap 2,05, B/C value in Kruwisan village 1,08 and Tlahap village 1,05, and also IRR value in Kruwisan village 29,44% and in Tlahap village 28,80%, and (4) Gini ratio value in Kruwisan village (monoculture) 0,273, Kruwisan village (tobacco + onion + livestock) 0,264, Tlahap village (tumpangsari) 0,365 and Tlahap village (tobacco + coffee + livestock) 0,250.